Evaluación de riesgos eléctricos en construcción de redes de medio voltaje de la EEASA, propuesta de un sistema de intervención para disminuir los accidentes eléctricos de la EEASA. - Barrera Flores, Jaime Marcelo (2013)
The present research work carries out an evaluation of electrical risks in the construction of medium voltage networks of the EEASA to reduce electrical accidents in these operations. This study was carried out on a population of 15 workers involved in this activity. The problem was addressed by carrying out an analysis of the significance of the accidents based on the number of hours worked using the NTP 236 determining the accumulated frequency index, and the limit line of accident rate for the corresponding year, then the qualitative matrix of triple consideration (Probability, Severity and Vulnerability) recommended by the Ecuadorian Ministry of Labor Relations was used to detect intolerable risk factors, detecting the percentage of moderate, important and intolerable risks, then To deepen the investigation, the critical activities were determined and the level of exposure, level of deficiency and level of probability were quantified according to the type of work, activity and corresponding task in the construction of medium voltage networks of the EEASA using the NTP 330 or simplified method of accident risk assessment.